Komitmen Beragama Islam Memprediksi Stabilitas Pernikahan - Rena Latifa (‎‎‎TAZKIYA Journal of Psychology, 2015)
Interest in religion and spirituality has increased dramatically recently both within culture in general and within psychology. Substantial literatures now describes connections between religion and mental health. The literature on marriage provided evidence that subjective and organizational religious participation was associated with enhanced family functioning and higher marital satisfaction (Wilson & Musick, 1996). In this study, we examine Islamic religious commitment on marital stability; with the underlying assumption that religious commitment may encourage couples to remain married. Islamic religious commitment in this study defined as the degree to which a person adheres to Islamic religious values, beliefs, and practices and uses them in daily living. Our findings indicated that religious commitment truly predict marital stability among newlywed couples.